Simultaneously achieving high energy density and responsivity in submicron BaTiO3 film capacitors integrated on Si - Jun Ouyang; Yinxiu Xue; Chuanqi Song; Meiling Yuan; Kun Wang; Yuyao Zhao; Hongbo Cheng; Hanfei Zhu; Chao Liu (Journal of Advanced Ceramics, 2024)
In the research field of energy storage dielectrics, the “responsivity” parameter, defined as the recyclable/recoverable energy density per unit electric field, has become critically important for a comprehensive evaluation of the energy storage capability of a dielectric. In this work, high recyclable energy density and responsivity, i.e., Wrec = 161.1 J·cm–3 and ξ = 373.8 J·(kV·m2)–1, have been simultaneously achieved in a prototype perovskite dielectric, BaTiO3, which is integrated on Si at 500 ℃ in the form of a submicron thick film. This ferroelectric film features a multi-scale polar structure consisting of ferroelectric grains with different orientations and inner-grain ferroelastic domains. A LaNiO3 buffer layer is used to induce a {001} textured, columnar nanograin microstructure, while an elevated deposition temperature promotes lateral growth of the nanograins (in-plane diameter increases from ~10–20 nm at lower temperatures to ~30 nm). These preferably oriented and periodically regulated nanograins have resulted in a small remnant polarization and a delayed polarization saturation in the film’s P–E behavior, leading to a high recyclable energy density. Meanwhile, an improved polarizability/dielectric constant of the BaTiO3 film has produced a much larger maximum polarization than those deposited at lower temperatures at the same electric field, leading to a record-breaking responsivity for this simple perovskite.